2018
DOI: 10.1038/s41467-018-06665-5
|View full text |Cite
|
Sign up to set email alerts
|

PWWP2A binds distinct chromatin moieties and interacts with an MTA1-specific core NuRD complex

Abstract: Chromatin structure and function is regulated by reader proteins recognizing histone modifications and/or histone variants. We recently identified that PWWP2A tightly binds to H2A.Z-containing nucleosomes and is involved in mitotic progression and cranial–facial development. Here, using in vitro assays, we show that distinct domains of PWWP2A mediate binding to free linker DNA as well as H3K36me3 nucleosomes. In vivo, PWWP2A strongly recognizes H2A.Z-containing regulatory regions and weakly binds H3K36me3-cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(74 citation statements)
references
References 66 publications
(105 reference statements)
2
66
0
Order By: Relevance
“…The majority of interactions with non-NuRD components was lost after Mbd3 deletion, indicating that most of these proteins do not directly associate either with the MTA proteins or with the deacetylase subcomplex ( Fig 1C). Exceptions to this were Zfp296, which was identified as interacting with all three MTA proteins in an Mbd3-independent manner, and Pwwp2a, which copurified with Mta1 in both wild-type and Mbd3-null cells, consistent with recent reports (Link et al, 2018;Zhang et al, 2018). Notably, Zfp219 and Zfp512b both showed Mbd3-independent interactions specifically with Mta2 ( Fig 1C).…”
Section: Mta Proteins Are Not Mutually Exclusive Within the Nurd Compsupporting
confidence: 90%
See 1 more Smart Citation
“…The majority of interactions with non-NuRD components was lost after Mbd3 deletion, indicating that most of these proteins do not directly associate either with the MTA proteins or with the deacetylase subcomplex ( Fig 1C). Exceptions to this were Zfp296, which was identified as interacting with all three MTA proteins in an Mbd3-independent manner, and Pwwp2a, which copurified with Mta1 in both wild-type and Mbd3-null cells, consistent with recent reports (Link et al, 2018;Zhang et al, 2018). Notably, Zfp219 and Zfp512b both showed Mbd3-independent interactions specifically with Mta2 ( Fig 1C).…”
Section: Mta Proteins Are Not Mutually Exclusive Within the Nurd Compsupporting
confidence: 90%
“…Functional and genetic data indicate that the CHD4‐containing remodelling subunit is capable of functioning independently of intact NuRD (O'Shaughnessy & Hendrich, ; O'Shaughnessy‐Kirwan et al , ; Ostapcuk et al , ). The deacetylase subcomplex has been shown biochemically to exist outside of intact NuRD, though whether this subcomplex has any specific function is not clear (Link et al , ; Zhang et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…The acquisition of additional copies of a gene through duplication events provides opportunities for the development of unique gene products with distinct regulatory mechanisms (2). Functional divergence can result from gene duplications and protein paralog identity can influence the composition of large protein complexes (3). However, the consequences of paralog switching are largely overlooked during the characterization of proteins, protein complexes, and protein interaction networks.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we demonstrated that the chromatin-binding protein PWWP2A, which can selectively recognize H2A.Z-containing nucleosomes (42,43), interacts robustly with the MTA, HDAC and RBBP subunits of NuRD. Surprisingly, however, GATAD2, MBD and CHD are not detected as interaction partners in these affinity-purification based experiments, suggesting that the two enzymatic activities in NuRD might in some situations be separable.…”
Section: Ino80mentioning
confidence: 99%
“…The subunit stoichiometry is also uncertain; recent studies using label-free mass spectrometry (33)(34)(35)(36)(37)(38) have yielded variable results that are often at odds with the stoichiometries demonstrated in the known subcomplex structures.The mechanisms by which NuRD selects target sites are also poorly understood. Transcriptional regulators such as FOG1 (22,39) and BCL11A (40,41) can bind to NuRD via the RBBP subunits but this mechanism is likely to account for only a small proportion of NuRD-genome interactions.Recently, we demonstrated that the chromatin-binding protein PWWP2A, which can selectively recognize H2A.Z-containing nucleosomes (42,43), interacts robustly with the MTA, HDAC and RBBP subunits of NuRD. Surprisingly, however, GATAD2, MBD and CHD are not detected as interaction partners in these affinity-purification based experiments, suggesting that the two enzymatic activities in NuRD might in some situations be separable.Against this background, we have used structural, biophysical and biochemical data to define the architecture of the NuRD complex.…”
mentioning
confidence: 99%